Mammalian integrated stress responses in stressed organelles and their functions - Lu Hao-jun; Koju Nirmala; Sheng Rui (Acta Pharmacologica Sinica, 2024)
The integrated stress response (ISR) triggered in response to various cellular stress enables mammalian cells to effectively cope with diverse stressful conditions while maintaining their normal functions. Four kinases (PERK, PKR, GCN2, and HRI) of ISR regulate ISR signaling and intracellular protein translation via mediating the phosphorylation of eukaryotic translation initiation factor 2 α (eIF2α) at Ser51. Early ISR creates an opportunity for cells to repair themselves and restore homeostasis. This effect, however, is reversed in the late stages of ISR. Currently, some studies have shown the non-negligible impact of ISR on diseases such as ischemic diseases, cognitive impairment, metabolic syndrome, cancer, vanishing white matter, etc. Hence, artificial regulation of ISR and its signaling with ISR modulators becomes a promising therapeutic strategy for relieving disease symptoms and improving clinical outcomes. Here, we provide an overview of the essential mechanisms of ISR and describe the ISR-related pathways in organelles including mitochondria, endoplasmic reticulum, Golgi apparatus, and lysosomes. Meanwhile, the regulatory effects of ISR modulators and their potential application in various diseases are also enumerated.